Implementation of Character Education in Islamic Education Institutions in Minority Areas (Case Study of Tana Toraja Muhammadiyah Development Islamic Boarding School) - Amirah Amirah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Islamic Education Institutions have a very important role in forming the character education of students, because the training carried out is predominantly oriented towards the principles of Islamic Education. This research aims to understand the concept of character education in Islamic education institutions in minority areas, namely at the Tana Toraja Muhammadiyah Development Islamic Boarding School. The research method used in this research is a method that combines quantitative and qualitative or is called a mixed method. This includes a philosophical basis, the use of quantitative and qualitative approaches, combining the two approaches in research. The combined research method was carried out so that comprehensive, valid, reliable and objective data could be obtained. It is hoped that this research can contribute to understanding the concept of character education in Islamic educational institutions in minority areas in institutions namely the Tana Toraja Muhammadiyah Development Boarding School. This research also examines the concept of character education between institutions that have very different cultures from one another. Based on the research results, the characters implemented at the Pembagunan Muhammadiyah Tana Toraja Islamic Boarding School are in the sufficient category, namely religious, honest, tolerant, disciplined and caring for the environment.